Animation of a Local Urban Community. Sebastian Latocha Talks to Remigiusz Kaczmarek, the Chairman of the Józef Montwiłł-Mirecki Community Council in Łódź - Latocha, Sebastian (Łódzkie Studia Etnograficzne, 2020)
How do you nurture common welfare in a modern city? What is the role of local urban communities and the networked cooperation of numerous bodies like community councils, district NGOs, neighbourhood initiatives and particular individuals (animators, activists, involved citizens) – in creating a community, which, being subject to the municipality’s activity, does not patiently await its fate, but takes matters into its own hands? What impact does the history, tradition, urban planning and architecture, local symbols, rituals and institutions of a location have on creating a sense of identity for that given place and for creating an atmosphere of education, animation and activity in the public sphere in cooperation ‘with’ (and not ‘for’) the local community? How do Community Councils support and develop neighbourhood communities? An interview with Remigiusz Kaczmarek, the Chairman of the Józef Montwiłł-Mirecki Community Council in Łódź, reveals how the difficult heritage of this district provided the residents with a model of collaboration and social participation. The case of this modernist housing estate constructed in Łódź before the Second World War shows the dynamics of urban local community development based on the common experience of its residents.